Perjuangan Kesetaraan Gender dalam Karya Sastra Kajian terhadap Novel Perempuan Berkalung Sorban dan Gadis Pantai - Moh Muzakka (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
The struggling of gender in the male hegemony challance were discussed often in discourse, a part is in literature. This paper was analyzed the gender struggle in two novel i.e. Perempuan Berkalung Surban (The Woman to wear a necklace of headdress) novel, that wrote by Abidah El-Khalieqy and Gadis Pantai (The Beach Girl) novel, that wrote by Pramoedya Ananta Toer. The first novel is wrote by a woman have pesantren ‘educational institute with a Moslem bacground’ background and second novel is wrote by a man have nasionalism-realism-socialist ideology. To analyze second novel have used sociology of literature and with feminist literature chritic approach.Result of analyze are shown that gender struggle in novel Perempuan Berkalung Sorban is backgrounded by male repressive against women base the explanation and interpretation of the verses from the Koran (Islam religion) that very patriarchal. As for the gender struggle in novel Gadis Pantai is backgrounded by male repressive against women base feudalistic tradition, the woman as private property of man. Standing point of feudalist, tirany, and have not to appraise or to value the women, then respond by women with gender struggle.